'Contact' Rock Art and the Hybrid Economy Model: Interpreting Introduced Subject Matter from Marra Country, Southwest Gulf of Carpentaria, Northern Australia. Issue 4 (November 2022) - Brady, Liam M.; Wesley, Daryl; Bradley, John; Kearney, Amanda; Evans, Shaun; Barrett, David
Abstract : Studies of introduced subject matter in rock-art assemblages typically focus on themes of cross-cultural interaction, change and continuity, power and resistance. However, the economic frameworks guiding or shaping the production of an assemblage have often been overlooked. In this paper we use a case study involving a recently recorded assemblage of introduced subject matter from Marra Country in northern Australia's southwest Gulf of Carpentaria region to explore their production using a hybrid economy framework. This framework attempts to understand the nature of the forces that shape people's engagement with country and subsequently how it is being symbolically marked as adjustments to country occur through colonization. We argue that embedding these motifs into a hybrid economy context anchored in the pastoral industry allows for a more nuanced approach to cross-cultural interaction studies and adds another layer to the story of Aboriginal place-marking in colonial contexts. This paper aims to go beyond simply identifying motifs thought to represent introduced subject matter, and the cross-cultural framework(s) guiding their interpretation, and instead to direct attention to the complex network of relations that potentially underpin the production of such motifs.